Evaluation of a new multiplex PCR assay (ParaGENIE G-Amoeba Real-Time PCR kit) targeting Giardia intestinalis, Entamoeba histolytica and Entamoeba dispar/Entamoeba moshkovskii from stool specimens: evidence for the limited performances of microscopy-based approach for amoeba species identification. (November 2018) - Morio, F.; Valot, S.; Laude, A.; Desoubeaux, G.; Argy, N.; Nourrisson, C.; Pomares, C.; Machouart, M.; Le Govic, Y.; Dalle, F.; Botterel, F.; Bourgeois, N.; et al.
Abstract: Objectives: Besides the potential to identify a wide variety of gastrointestinal parasites, microscopy remains the reference standard in clinical microbiology for amoeba species identification and, especially when coupled with adhesin detection, to discriminate the pathogenic Entamoeba histolytica from its sister but non-pathogenic species Entamoeba dispar / Entamoeba moshkovskii . However, this approach is time-consuming, requires a high-level of expertise that can be jeopardized considering the low prevalence of gastrointestinal parasites in non-endemic countries. Here, we evaluated the CE-IVD-marked multiplex PCR (ParaGENIE G-Amoeba, Ademtech) targeting E. histolytica and E. dispar / E. moshkovskii and Giardia intestinalis . Methods: This evaluation was performed blindly on a reference panel of 172 clinical stool samples collected prospectively from 12 laboratories and analysed using a standardized protocol relying on microscopy (and adhesin detection by ELISA for the detection of E. histolytica ) including G. intestinalis ( n = 37), various amoeba species ( n = 55) including E. dispar ( n = 15), E. histolytica ( n = 5), as well as 17 other gastrointestinal parasites ( n = 80), and negative samples ( n = 37). Results: This new multiplex PCR assay offers fast and reliable results with appropriate sensitivity and specificity for the detection of G. intestinalis and E. dispar / E. moshkovskii from stools (89.7%/96.9% and 95%/100%, respectively). Detection rate and specificity were greatly improved by the PCR assay, highlighting several samples misidentified by microscopy, including false-negative and false-positive results for both E. dispar/E. moshkovskii and E. histolytica . Conclusion: Given the clinical relevance of amoeba species identification, microbiologists should be aware of the limitations of using an algorithm relying on microscopy coupled with adhesin detection by ELISA.